The diagnostic pathway to a surgical lymph node excision biopsy service in a HIV and TB endemic region in a Western Cape Tertiary Institution - Potelwa, Tennis Tomo Camagu (Department of Medicine, 2026)
In the HIV/TB endemic public care setting of the Western Cape, diagnostic consideration of patients with persistent lymphadenopathy is focused towards extra- pulmonary tuberculosis (EPTB), more than other infectious or malignant causes of lymphadenopathy. We investigated patients consecutively referred for lymph node excision at Groote Schuur Hospital for selection of, and results of, laboratory tests performed during the diagnostic pathway and possible impact on diagnostic delay. Eighty-six patients were included, 61 patients (71%) had no previous diagnosis to explain the lymphadenopathy, while 25 patients had a previous diagnosis of a haematological malignancy, cancer or tuberculosis. In the new patient group, EPTB was the commonest diagnostic outcome (24.6%, 15/61), followed by lymphoma (21.3%, 13/61) and cancer (14.8%, 9/61). HIV positive patients constituted 41% (n=25). Median time from presentation with lymphadenopathy to first excision biopsy was 55 days (IQR 22-106). Fine needle aspiration (FNA) cytology of lymphadenopathy was performed in 30/61 (49%) of patients and repeated in a third of these, while smear for AFBs and culture for M. tuberculosis were infrequently performed and GeneXpert MTB/RIF assay on FNA never performed. Furthermore, in the seven patients with a final diagnosis of lymphoma in whom FNA cytology was performed, cytology was not diagnostic of lymphoma. In patients with persistent lymphadenopathy, this study demonstrates how poorly structured diagnostic pathways contribute to unnecessary health care utilisation and diagnostic delay in readily treatable conditions. We need to implement accurate diagnostic pathways for patients with lymphadenopathy in South Africa's healthcare system, thus improving early diagnosis of both EPTB and lymphoma, potentially improving patient outcomes.